A Personal Reflection on Law Teaching, or How I Became an Establishment Insider on the Outside - Olivas, Michael A. (Radical Teacher, 2014)
I assume that not all readers are au courant with the so-called crisis in legal education. Therefore, it may be useful to offer a brief description of the current problems of the legal profession and the consequent debate occurring among legal educators, bar officials, judges, and lawyers.